CORRELATION BETWEEN TYPES OF MINDSET AND QUALITY OF LIFE EVALUATION IN PATIENTS WITH SCOLIOSIS - WESLEY WILIAN COSTA MARTINS; LEONARDO SARDAS; RODOLFO GUEDES PEREIRA NUNES BARBOSA; RODRIGO GÓES MEDÉA DE MENDONÇA; ALBERTO GOTFRYD; MARIA FERNANDA SILBER CAFFARO; PATRÍCIA MARIA DE MORAES BARROS FUCS; ROBERT MEVES (Acta Ortopédica Brasileira, 2023)
ABSTRACT Scoliosis is a pathology with multiple etiologies that leads to aesthetic changes, increased morbidity and, especially, psychological damage. Objective: This work aims to compare two mindset types (fixed and growth) and assess levels of quality of life in individuals with scoliosis. Methods: Two questionnaires, Scoliosis Research Society-30 (SRS-30) and Early-Onset Scoliosis-24 Questionnaire (EOSQ-24), associated with the “Health Mindset Scale,” were used. We applied the SRS-30 to patients who were independent or whose diagnosis of spinal deformity occurred after the age of 10 years. For patients diagnosed before the age of 10 or who presented dependence due to cognitive impairment, caregivers were subjected to the “Health Mindset Scale” and EOSQ-24 questionnaires. Results: The sample consisted of 35 patients aged from 4 to 46 years, the majority aged from 15 to 18 years old (42.9%), female (71.4%), and with neuromuscular scoliosis (28.6%). The only significant result (p = 0.060) was the increase in pain/discomfort scores in the EOSQ-24 for a patient with a growth mindset. Lastly, there was no statistical difference between groups, however, in patients with a growth mindset, there was a tendency (p = 0.060) to have a higher pain/discomfort score, assessed via the EOSQ-24 score, reported by the caregiver. Level of Evidence III, Retrospective Comparative Study.